2017
DOI: 10.1590/abd1806-4841.20176157
|View full text |Cite
|
Sign up to set email alerts
|

Yellow dots in trichoscopy: relevance, clinical significance and peculiarities

Abstract: Yellow dots are follicular ostium filled with keratin and/or sebum. Initially, they were exclusively associated with alopecia areata. Currently they have also been described in androgenetic alopecia, chronic cutaneous (discoid) lupus erythematosus, and dissecting cellulitis. Due to the growing importance of trichoscopy and its findings in the evaluation of the scalp, this article describes the main diseases in which yellow dots are a common trichoscopic finding, highlighting its characteristics in each dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
1
17
1
1
Order By: Relevance
“…We suggest this disparity also could be due to the disease duration, as yellow dots represent follicular Ostia (atrichia) due to sebaceous gland persistence after severe miniaturization of the follicles or sebaceous gland hyperplasia under the influence of androgens, which indicate chronicity, and this was confirmed in our study as all patients having yellow dots were of long disease duration >6 months. This was confirmed also by earlier study by Lima et al, who suggested that yellow dots are seen in more advanced stages of the disease with sebaceous component predominance over keratotic elements, differing from the other dermatosis, in which keratinocytic materials are predominant.…”
Section: Discussionsupporting
confidence: 91%
“…We suggest this disparity also could be due to the disease duration, as yellow dots represent follicular Ostia (atrichia) due to sebaceous gland persistence after severe miniaturization of the follicles or sebaceous gland hyperplasia under the influence of androgens, which indicate chronicity, and this was confirmed in our study as all patients having yellow dots were of long disease duration >6 months. This was confirmed also by earlier study by Lima et al, who suggested that yellow dots are seen in more advanced stages of the disease with sebaceous component predominance over keratotic elements, differing from the other dermatosis, in which keratinocytic materials are predominant.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding scalp severity, S2 grade of severity represented 45% of the patients, followed by Grade S1 in 31% of patients, these findings are also documented in other studies 12,13 . There are several dermoscopic signs of alopecia areata including YDs, BDs, SVHs, EHs, and BHs (8,9,14). YDs were the commonest dermatoscopic sign noticed in this work.…”
Section: Discussionmentioning
confidence: 52%
“…They are observed as rounded or polycyclic structures with colors ranging from pinkish to brownish yellow. 4 This finding has been detected in various diseases, such as alopecia areata, chronic cutaneous lupus erythematosus, androgenetic alopecia, and dissecting cellulitis and, less frequently, in trichotillomania. 5 Therefore, the brownish yellow dots identified in the present case are not specific to follicular mucinosis.…”
Section: Discussionmentioning
confidence: 91%